Rosette‐forming glioneuronal tumours are midline, FGFR1‐mutated tumours. (23rd March 2022) - Appay, Romain; Bielle, Franck; Sievers, Philipp; Barets, Doriane; Fina, Frédéric; Boutonnat, Jean; Adam, Clovis; Gauchotte, Guillaume; Godfraind, Catherine; Lhermitte, Benoît; Maurage, Claude‐Alain; Meyronet, David; et al.
Abstract: Aim: Rosette‐forming glioneuronal tumour (RGNT) is a rare central nervous system (CNS) World Health Organization (WHO) grade 1 brain neoplasm. According to the WHO 2021, essential diagnostic criteria are a 'biphasic histomorphology with neurocytic and a glial component, and uniform neurocytes forming rosettes and/or perivascular pseudorosettes associated with synaptophysin expression' and/or DNA methylation profile of RGNT whereas ' FGFR1 mutation with co‐occurring PIK3CA and/or NF1 mutation' are desirable criteria. Material and methods: We report a series of 46 cases fulfilling the essential pathological diagnostic criteria for RGNT. FGFR1 and PIK3CA hotspot mutations were searched for by multiplexed digital PCR in all cases, whereas DNA methylation profiling and/or PIK3R1 and NF1 alterations were analysed in a subset of cases. Results: Three groups were observed. The first one included 21 intracranial midline tumours demonstrating FGFR1 mutation associated with PIK3CA or PIK3R1 ( n = 19) or NF1 ( n = 1) or PIK3CA and NF1 ( n = 1) mutation. By DNA methylation profiling, eight cases were classified as RGNT (they demonstrated FGFR1 and PIK3CA or PIK3R1 mutations). Group 2 comprised 11 cases associated with one single FGFR1 mutation. Group 3 included six cases classified as low‐grade glioma (LGG) other than RGNT (one‐sixth showed FGFR1 mutation and one a FGFR1 and NF1 mutation) and eight cases without FGFR1 mutation. Groups 2 and 3 were enriched in lateral and spinal cases. Conclusions: We suggest adding FGFR1 mutation and intracranial midline location as essential diagnostic criteria. When DNA methylation profiling is not available, a RGNT diagnosis remains certain in cases demonstrating characteristic pathological features and FGFR1 mutation associated with either PIK3CA or PIK3R1 mutation. Abstract : Rosette‐forming glioneuronal tumour (RGNT) is a rare central nervous system World Health Organization grade 1 midline, FGFR1‐mutated glioneuronal tumour equally affecting male and female and typically occurring between 10 and 40 years. Histopathological features are not sufficient to reach RGNT diagnosis. DNA methylation profiling is the most reliable way to reach RGNT diagnosis; when lacking, a diagnosis is certain in cases demonstrating characteristic pathological features and a FGFR1 mutation associated with either PIK3CA mutation or less frequently PIK3R1 mutation.